Population Growth on the Environment: A Short Review - Nguyen Van Dao, Vu Hong Van (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Population and environment are two closely related factors. The development of one factor is related to the development of another factor, namely: The change of the population has a positive or negative impact on the environment and a sustainable or unsustainable development environment resources also have the opposite effect in human society by both sides. Especially in the current socio-economic development trend, the above relationship is shown more clearly. Vietnam is a developing country with very rapid population growth, accompanied by an increase in environmental pollution to an alarming level, especially in the two largest cities of the country, Hanoi and Ho Chi Minh City. From the field survey, this study shows the effects of population growth on environmental issues such as air pollution, water pollution, destruction of forest resources, increased land use, etc.; since then, it is recommended to limit the population growth and use the resources (not renewable) appropriately for sustainable development in the future